How to possess an electronic bill of lading as information? A comparative perspective of the legislation on the “possession problem” of electronic bills of lading - Sun, Siqi; He, Ran (Frontiers in Marine Science, 2024)
The possession of the paper B/Ls is the basis of the function of a B/L as a document of title in common law systems and the delivery effect of B/Ls in civil law systems. The “possession problem” of eB/Ls is how to ensure that eB/Ls, as intangible objects, continue to have this basis. In the international level, the MLETR creates the concept of “control” of electronic transferable records as a functional equivalent to possession of paper B/Ls. Although the CMI Rules and the Rotterdam Rules involve control, neither of them makes specific provisions for control. In the national level, there are three solutions to the “possession problem”: First, expand the objects of possession to cover eB/Ls, such as the United Kingdom. Second, adopt the same approach as the MLETR, creating a concept of control as a functional equivalent of possession, such as Singapore and Japan, which is in the process of legislating, as well as Abu Dhabi Global Market and other 6 jurisdictions which have directly transplanted Article 11 of the MLETR. Third, establish a central registry system so that possession of eB/Ls does not have to be demonstrated. A typical example is South Korea, where the legislation on eB/Ls preceded the MLETR. The revision of Chinese Maritime Code currently does not pay sufficient attention to the “possession problem” of eB/Ls. The countermeasure should be to first stipulate the delivery effect of paper B/Ls, and then provide a solution to the “possession problem” of eB/Ls.